Improving Speaking Skill the Fourth Semester PGSD Students of STKIP Al Maksum Through Dialogue Technique - Yusrah Yusrah (The Seall Journal, 2023)
Speaking is considered a necessary skill because of its essential role in facilitating students to master English. It enables students to express themselves creatively, imaginatively and to communicate with others effectively. To master speaking ability, the fourth-semester PGSD Students must be trained to use English in communication orally. One of the appropriate and comprehensive strategies for teaching speaking is Dialogue Technique. The objective of this study is to find out whether the fourth-semester PGSD students’ speaking skill improves after being taught through Dialogue Technique or not. The strategy applied in this study was the aspect of speaking and dialogue techniques. This study was conducted by using Quantitative Research. This study was done on the Fourth Semester PGSD Students of STKIP Al Maksum. There were 36 students taken as the sample in this study. The data were collected by giving speaking tests to the students. The result of the test showed that the mean score of the post-test was higher than the mean score of the pre-test which was from 70 become 78.75. This means students’ speaking skill was improved after being thought by using Dialogue Technique. Keywords: Improving, Speaking Skills, Dialogue Technique